Brand i Fulufjällets nationalpark - Sander, Jenny (2005)
Fire has historically been of great ecological importance in the boreal forests of Sweden. The forest fire regime has, however, varied between different parts of the country. The objective of this thesis is therefore to investigate the fire history in Fulufjället National Park and, on this basis, give suggestions for future fire management.